Developing syntactic complexity and accuracy in EFL students’ essays through sentence combining - Jaya, Sinarman; Susyla, Dian; Melati (Indonesian Journal of Educational Development (IJED), 2025)
Many EFL students face challenges in developing syntactic complexity and grammatical accuracy in academic writing. Sentence combining, which involves merging simple sentences into more complex ones, has shown promise in enhancing grammatical control and writing fluency. However, research on its effectiveness in EFL contexts, particularly in improving syntactic variety and grammatical accuracy, is still limited. This quasi-experimental study investigated the impact of sentence combining on syntactic variety and grammatical accuracy in academic essays written by undergraduate EFL students. The participants were 40 students from the English Education Study Program at Universitas Muhammadiyah Bengkulu, selected using purposive sampling. Over one semester, the experimental group received sentence combining instruction, while the control group followed conventional writing instruction. Pre- and post-test essays were analyzed using three syntactic measures: Mean Length of T-unit (MLT), Clauses per T-unit (C/T), and Dependent Clauses per Clause (DC/C). The findings revealed statistically significant improvements in all three dimensions of syntactic complexity for the experimental group. These results demonstrate the effectiveness of sentence combining in developing EFL students’ academic writing. It is recommended that writing instructors integrate sentence combining into academic writing curricula to support syntactic development and grammatical precision.